Duas ou três coisas sobre Antonio Candido - Musse, Ricardo [UNESP] (Universidade Estadual Paulista (Unesp), Departamento de Filosofia, 1995)
Busca-se aqui investigar a conexão entre duas características definidoras da originalidade crítica de Antonio Candido: sua filiação à linhagem do marxismo ocidental e sua inserção numa tradição nacional.

The aim of this paper is to discuss the connection between two basic traces grounding the originality of Antonio Candido's literary criticism: firstly, its insertion into the mainstraim of western marxism and, secondly, into national (Brasilian) tradition.
Two or three things about Antonio Candido
Keywords: Crítica; literatura; vida social; tradição nacional; dialética; marxismo ocidental; Literary criticism; literature; social life; national tradition; dialectics; western marxism